Paths to Competence in Listening Comprehension - Krashen, Stephen; Renandya, Willy A.; Mason, Beniko; Bose, Pratheeba (Beyond Words, 2018)
We present two paths to increasing listening comprehension ability, one in-class and other in the country where the language is spoken. In both cases, we predict that those with higher reading ability in the second language will progress faster.